Challenging The Principle of Equality Before the Law in Qanun Jinayat Aceh - Khairil Akbar; Nyak Fadhlullah; Zahlul Pasha Karim (Media Syari'ah : Wahana Kajian Hukum Islam dan Pranata Sosial, 2022)
This article aims to explain how the principle of equality before the law in Aceh Qanun Number 6 of 2014 concerning the Jinayat Law is applied. As part of the Indonesian state, the application of Islamic law (especially in the jinayat) in Aceh should be in line with the characteristics of the rule of law, among which is the principle of equality before the law. Through the statute approach, it turns out that there is a disparity between the Qanun Jinayat Aceh and the regulations above, including the principle of equality before the law. Even though they have equaled men and women, the Qanun Jinayat Aceh clearly distinguishes people based on their religion. A person who is Muslim is obliged to submit to Qanun a quo while those who are not Muslim are in two choices: first, subject to Qanun because of the vacuum of national law; or second, choosing to submit to the Qanun because it is considered lighter than national law. This situation is discriminatory for Muslims on one hand, and unfair to non-Muslims on the other.Artikel ini bertujuan untuk menjelaskan bagaimana prinsip equality before the law dalam Qanun Aceh Nomor 6 Tahun 2014 tentang Hukum Jinayat diterapkan. Sebagai bagian dari negara Indonesia, penerapan syariat Islam (khususnya di bidang jinayat) di Aceh sudah seharusnya tetap sejalan dengan ciri negara hukum yang di antaranya adalah adanya prinsip equality before the law. Melalui pendekatan perundang-undangan (statute approaceh), ternyata didapati adanya disparitas antara Qanun Jinayat Aceh dengan peraturan di atasnya, termasuk terhadap prinsip equality before the law. Meski telah menyejajarkan laki-laki dan perempuan, namun Qanun Jinayat Aceh ini secara tegas membedakan seseorang berdasarkan agama yang dianutnya. Seorang yang beragama Islam wajib tunduk pada Qanun a quo sedangkan mereka yang beragama bukan Islam berada pada dua pilihan: pertama, tunduk terhadap Qanun karena kekosongan hukum nasional; atau kedua, memilih tunduk terhadap Qanun karena dirasa lebih ringan dibanding hukum nasional. Keadaan ini diskriminatif bagi orang Islam di satu pihak, dan tidak adil bagi nonmuslim di pihak lain.